2021
DOI: 10.3389/fmed.2021.780087
|View full text |Cite
|
Sign up to set email alerts
|

Hypercalciuria in Postmenopausal Women With Reduced Bone Mineral Density Is Associated With Different Mineral Metabolic Profiles: Effects of Treatment With Thiazides and Anti-resorptives

Abstract: Hypercalciuria may represent a challenge during the workup for osteoporosis management. The present study aimed: (1) to describe the phenotype associated with hypercalciuria in vitamin D-sufficient (serum 25 hydroxyvitamin D (25OHD) > 20 ng/ml) patients with osteopenia/osteoporosis; (2) to analyze the effects of thiazides and anti-resorptive drugs on urine calcium excretion (UCa), mineral metabolic markers, and bone mineral density. Seventy-seven postmenopausal women with hypercalciuria (Uca > 4.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…15 Both alteration in bone metabolism (whether as a primary condition or as a response to the buffering of the acid load) and direct tubular calcium leak generated by dietary proteins likely play pivotal roles in increased calciuria and lithogenesis. 22 Such patients with stone benefit from drugs typically used for preventing stones (thiazides, citrate) because they are effective on both bone turnover [23][24][25] and agents generally used for the treatment of osteoporosis, some of which (e.g., bisphosphonates) are known to reduce calciuria 26 and stone occurrence. 27 Stratification of stone formers according to osteoporosis/ osteopenia risk, depending on the existence of one or more conditions, such as medullary sponge kidney, distal renal tubular acidosis, primary hyperparathyroidism, malabsorptive syndromes and fasting hypercalciuria, and/or the results of bone densitometry, may help when opting for long-term treatment of stone-forming patients.…”
Section: Reasons For Prolonged Kidney Stone Prophylaxis Beyond Kidney...mentioning
confidence: 99%
See 1 more Smart Citation
“…15 Both alteration in bone metabolism (whether as a primary condition or as a response to the buffering of the acid load) and direct tubular calcium leak generated by dietary proteins likely play pivotal roles in increased calciuria and lithogenesis. 22 Such patients with stone benefit from drugs typically used for preventing stones (thiazides, citrate) because they are effective on both bone turnover [23][24][25] and agents generally used for the treatment of osteoporosis, some of which (e.g., bisphosphonates) are known to reduce calciuria 26 and stone occurrence. 27 Stratification of stone formers according to osteoporosis/ osteopenia risk, depending on the existence of one or more conditions, such as medullary sponge kidney, distal renal tubular acidosis, primary hyperparathyroidism, malabsorptive syndromes and fasting hypercalciuria, and/or the results of bone densitometry, may help when opting for long-term treatment of stone-forming patients.…”
Section: Reasons For Prolonged Kidney Stone Prophylaxis Beyond Kidney...mentioning
confidence: 99%
“… 15 Both alteration in bone metabolism (whether as a primary condition or as a response to the buffering of the acid load) and direct tubular calcium leak generated by dietary proteins likely play pivotal roles in increased calciuria and lithogenesis. 22 Such patients with stone benefit from drugs typically used for preventing stones (thiazides, citrate) because they are effective on both bone turnover 23 25 and agents generally used for the treatment of osteoporosis, some of which ( e.g. , bisphosphonates) are known to reduce calciuria 26 and stone occurrence.…”
Section: Reasons For Prolonged Kidney Stone Prophylaxis Beyond Kidney...mentioning
confidence: 99%
“… 11 There are also a multitude of drugs that interfere with the absorption and/or metabolism of vitamin D; the most characteristic are carbamazepine, cimetidine, cholestyramine, colestipol, thiazide diuretics, phenytoin, phenobarbital and valproate. 12 , 13 , 14 , 15 , 16 …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we aimed to determine the relationship between a history of kidney stones and human bone health. As many patients with kidney stones have hypercalciuria, clinicians are concerned that their bone mineral density (BMD) may be reduced, which has inspired several recent studies 5–8. Although many studies have found that the occurrence of kidney stones is associated with a decreased BMD, the results remain inconclusive.…”
Section: Introductionmentioning
confidence: 99%